Study of Nosocomial Clostridium Difficile Diarrhea by Culture and Tissue Culture Methods - MH Salari; N Sadeghifard; MR Ghassemi; F Amin Harati; S Ghorchian (Tehran University of Medical Sciences, 2007)
Background: Clostridium difficult is an identified cause of antibiotic-associated diarrhea, antibiotic-associated colitis, pseudomembranous colitis and nosocomial diarrhea. The purpose of this study was to investigate the prevalence of nosocomial C. difficile-associated diarrhea in Tehran University of Medical Science Hospitals. Methods: In this study a total of 942 stool samples from patients with nosocomial diarrhea that were hospitalized in Imam Khomeini hospital, Shariati hospital and Children clinical center were collected. The samples were cultured on a selective cycloserine cefoxitin fructose agar (CCFA) and incubated in anaerobic conditions, at 37 °C for 5 days. Isolated C. difficile by conventional biochemical tests, bacterial cytotoxicity by Vero tissue culture and antimicrobial sensitivity to antibiotics by Kirby Bauer method (disk diffusion) were investigated. Results: Of the total patients, 57 Toxigenic C. difficile (6.1%) were isolated. Results of statistical analysis show significant differences between the rate of isolated Toxigenic C. difficile and age group of patients (P< 0.05). Among the units of selected hospitals, Toxigenic C. difficile was isolated most frequently in gastroenterology of Children clinical center. Meanwhile, the isolated Toxigenic C. difficile were sensitive to vancomycin, Chloramphenicol and ceftriaxone. Conclusion: Our findings show that, Toxigenic C. difficile was found in 6.1% hospitalized patients. Therefore, further studies to evaluate the role of Toxigenic C. difficile in nosocomial diarrhea processes, ecological and pathogenic terms by culture, Tissue culture and molecular methodes are suggested.